(untitled) (Fiep Bulletin - online, 2016)
Introduction: Diseases cause important physical, cognitive and socioeconomic damage. It is spread by steady population mobility in border regions. Objective: To describe the case incidence of the four endemic diseases considered neglected - tuberculosis, dengue, leprosy and malaria - in the city of Foz do Iguaçu in 2006. Method: This is a descriptive quantitative study. The data search was performed in the Information System for Notifiable Diseases. The variables used in this study were: number of new cases, sex and age group, in 2006. Results: The incidence of reported cases in males was higher for tuberculosis (58.2%) and malaria (77.1%), with no gender difference in the incidence of dengue cases and the presence of more females in the incidence of leprosy cases (54.2%). The age group that was most affected by the diseases in this study generally focused on the 20-59 years population. Conclusion: The location, the intense flow of people in the study region, among other factors, facilitates the occurrence of neglected diseases. Thus, knowledge about the epidemiology of these diseases is necessary to implement strategies to prevent diseases and improve quality of life.